Exploring the Spatial Dynamics of FEW Nexus Policies and Their Impact on Income Inequality Using Spatial Econometric Models: Evidence from Southeast Asian Countries - Khamjalas, Khambai (International Journal of Economics and Financial Issues, 2024)
This research investigates the spatial dynamics of Food, Energy, and Water (FEW) Nexus policies in Southeast Asian countries, analyzing their impact on income inequality. Utilizing spatial econometric models, the study explores intricate spatial patterns and employs spatial lag models along with a panel Granger causality test. Examining data from variables such as population, urbanization, life expectancy, GDP, HDI, CO2 Emission and energy consumption, our findings reveal significant spatial dependencies and causal relationships. The study enhances understanding of spatial dimensions in policy impacts for sustainable development, offering valuable insights for targeted FEW Nexus interventions to address income inequality in Southeast Asia.